2017
DOI: 10.3390/ijerph14101120
|View full text |Cite
|
Sign up to set email alerts
|

Mercury, Fatty Acids Content and Lipid Quality Indexes in Muscles of Freshwater and Marine Fish on the Polish Market. Risk Assessment of Fish Consumption

Abstract: Mercury content and fatty acids in muscles of Perca fluviatilis L. (European perch), Leuciscus idus L. (ide), Cyprinus carpio L. (European or common carp), Oncorhynchus mykiss Walb. (rainbow trout), Platichthys flesus L. (European flounder). and Clupea harengus L. (bream) from the Polish market were investigated. The total mercury was processed with AAS. The fatty acids were analyzed by gas chromatography. The concentration of mercury in muscles varied from 0.006 to 0.138 mg/kg and decreased as follows: perch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
58
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 55 publications
10
58
3
Order By: Relevance
“…Different studies reported that values of IA and IT, the meat‐lipid quality parameters, should not be more than 1.00 for human health (Chávez‐Mendoza et al ; Łuczynska, Paszczyk, Nowosad, & Łuczynski, ) and high H/H ratio in fish meat is considered to be more beneficial for human health (Fernandes et al, ). In this study, fish meat IA and IT values were lower than 1.00 and H/H ratios were high in both the beginning and end of the study and these values were sufficient for human health according to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies reported that values of IA and IT, the meat‐lipid quality parameters, should not be more than 1.00 for human health (Chávez‐Mendoza et al ; Łuczynska, Paszczyk, Nowosad, & Łuczynski, ) and high H/H ratio in fish meat is considered to be more beneficial for human health (Fernandes et al, ). In this study, fish meat IA and IT values were lower than 1.00 and H/H ratios were high in both the beginning and end of the study and these values were sufficient for human health according to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…LOD is the lowest value that can be detected with the given analytical procedure and based on statistical significance. The parameters of the method are described in the previous publications [ 37 , 42 ]. The quality of the method was tested using the reference material: BCR CRM 422 (muscles of cod Gadus morhua (L.)) with a certified value of mercury.…”
Section: Methodsmentioning
confidence: 99%
“…The atherogenicity index (AI) and the thrombogenicity index (TI) (AI and TI, respectively) were calculated as presented by Łuczyńska et al [ 37 ], Ulbricht and Southgate [ 50 ], Garaffo et al [ 51 ] and Telahigue et al [ 52 ]. The flesh-lipid quality (FLQ) indicating the percentage correlation between EPA + DHA and the total lipids was determined using the formulae by Łuczyńska et al [ 37 ], Abrami et al [ 53 ] and Senso et al [ 54 ]. The formulae used to calculate the hypercholesterolemic (OFA) and hypocholesterolemic (DFA) fatty acids are presented in the publication of Łuczyńska et al [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations